Effect of Perceived Ease of Use of Technology on Employees’ Performance in The Oil and Gas Sector - Precious Bolanle BOLODEOKU; Ebeguki Ebe IGBINOBA; Charles Kelechi CHUKWUDI; Sandra Efeomo IDIA; Samuel Olayemi OMOLAJA; Uduakobong Samuel UDOKEONG (Communications of International Proceedings, 2021)
This study appraises the effect of perceived ease of use of technology on performance of employees in the Nigerian oil and gas sector. The drive for the study was to determine if perceived ease of use of technology was adopted in ODENL plc and the oil and gas sector in Nigeria. Also, if perceived ease of use of technology has contributed to the performance of employees which in a large extent would yield high organisational productivity. Considerably, organisations fail to ensure proper and required training for employees to perceive the ease of using these technologies adopted by the organisation. As a result, this has led to a downward turn of the level of commitment in the oil and gas sector The population of the study used was 124, being the total staff strength of offshore workers in ODENL plc. A descriptive research design was used in this study along-side a mono-method. Specifically, this research used quantitative method (questionnaire) for collection of data and Structural Equation Modelling (SMART-PLS) was used to analyze the data collected. The result of the study revealed that perceived ease of use of technology has significant effect on the performance of employees in the oil and gas sector. However, the findings depicted those null hypotheses was rejected and there was a direct significant effect between perceived ease of use and employee performance.
Keywords: Perceived ease of use of technology; Oil and gas sector; Employee performance; Technological acceptance model